The Role of HLAC and NK Cells in Fetal Growth Restriction - Sulistyawati, Sri; Trimulya, Didon M; Respati, Supriyadi H; Soetrisno, Soetrisno (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To determine the role of HLA-C and NK cell expressions in fetal growth restriction (FGR). Methods: A cross sectional study design was used. This study was conducted at the Obstetrics and Gynecology Department of Dr. Moewardi General Hospital, Surakarta, its affiliated hospitals, and at the Pathological Anatomy Laboratory of the Faculty of Medicine, University of Sebelas Maret Surakarta. A total of 40 samples were included in this study. The samples consisted of 20 normal pregnancies and 20 pregnancies with FGR. HLA-C expression in the trophoblast and NK cells in decidua of the subjects who met the inclusion and exclusion criteria were examined using immunohistochemical method and statistical analysis with T test. Results: The mean expression of HLA-C in the trophoblast in the pregnant group with FGR was 9.021.30, normal pregnancy was 7.96 ± 0.97, p=0.01 (p<0.05). The mean expression of NK cells in decidua of pregnancy with FGR was 10.59 ± 2.11, normal pregnancy was 0.91 ± 8.18, with p=0.00 (p<0.05). Conclusion: The expressions of HLA-C in trophoblast and NK cells in decidua of pregnancy with FGR were higher compared with those of normal pregnancy. [Indones J Obstet Gynecol 2017; 5-3: 142-148] Keywords: fetal growth restriction, HLA-C, NK cells